2008
DOI: 10.1002/term.63
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic proteins in tissue engineering: the road from the laboratory to the clinic, part I (basic concepts)

Abstract: Discovered in 1965, bone morphogenetic proteins (BMPs) are a group of cytokines from the transforming growth factor-beta (TGFbeta) superfamily with significant roles in bone and cartilage formation. BMPs are used as powerful osteoinductive components of diverse tissue-engineering products for the healing of bone. Several BMPs with different physiological roles have been identified in humans. The purpose of this review is to cover the biological function of the main members of BMP family, the latest research on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
247
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 275 publications
(251 citation statements)
references
References 169 publications
(212 reference statements)
2
247
0
2
Order By: Relevance
“…Among these, bone morphogenetic proteins (BMPs) are probably the most important GFs involved [6,7,50]. BMPs regulate osteogenesis at two different levels: (1) the commitment of skeletal progenitor cells and (2) the maturation of osteoblasts in postnatal development [54].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, bone morphogenetic proteins (BMPs) are probably the most important GFs involved [6,7,50]. BMPs regulate osteogenesis at two different levels: (1) the commitment of skeletal progenitor cells and (2) the maturation of osteoblasts in postnatal development [54].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of an entirely unique family of growth factors, bone morphogenetic proteins (BMPs), has led to an increase in the understanding of bone formation and regeneration (15). BMPs regulate cartilage and bone differentiation in the body as initiated by the binding of BMPs to specific cell-surface receptors (bone morphogenic protein receptors).…”
mentioning
confidence: 99%
“…BMPs regulate cartilage and bone differentiation in the body as initiated by the binding of BMPs to specific cell-surface receptors (bone morphogenic protein receptors). This activates a signalling cascade inside the cells that results in the production and recruitment of proteins necessary for transformation into cartilage-and bone matrix-synthesizing cells, i.e., chondroblasts and osteoblasts, respectively (15). Bone formation or ossification continues through a series of events that include formation of cartilage, hypertrophy, and calcification of the deposited cartilage, vascular invasion, differentiation of osteoblasts and mineralization of bone.…”
mentioning
confidence: 99%
“…Although recombinant human (rh)BMP2 is the most widely utilized recombinant BMP with Food and Drug Administration (FDA)'s approval (Bessa, Casal, & Reis, 2008a, 2008b; Carreira et al, 2014), many investigators remain surprised to learn that other BMPs have previously been characterized as more osteogenic than the currently approved BMP2 or BMP7 (Kang et al, 2004). In two pioneering study conducted over a decade ago investigating all 14 BMPs, it was found that BMP6 and BMP9 stimulated the highest alkaline phosphatase (ALP) expression in vitro (Cheng et al, 2003) and had greater potential for orthotropic ossification in vivo (Kang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%